Gut Microbial Alterations in Diarrheal Baer's Pochards (Aythya baeri) - Xi, Li; Qin, Xinxi; Song, Yumin; Han, Jincheng; Li, Zhiqiang; Zhang, Jinliang (Frontiers in Veterinary Science, 2021)
The structure and composition of gut microbiota correlate with the occurrence and development of host health and disease. Diarrhea can cause the alterations of gut microbiota in animals, and the changes of gut microbial structure and composition may affect the development of diarrhea. However, there is a scarcity of information on the effects of diarrhea on gut fungal composition and structure, particularly in Baer's Pochard (Aythya baeri). The current study was performed for high-throughput sequencing of the fungal-specific internal transcribed spacer 1 (ITS-1) to detect the differences of gut mycobiota in healthy and diarrheal Baer’s Pochard. Results showed that the gut mycobiota not only decreased significantly in diversity but also in structure and composition. Statistical analysis between two groups revealed a significant decrease in the abundance of phylum Rozellomycota, Zoopagomycota, Mortierellomycota, and Kickxellomycota in diarrheal Baer's Pochard. At the genus levels, fungal relative abundance changed significantly in 95 genera, with 56 fungal genera like Wickerhamomyces, Alternaria, Penicillium, Cystofilobasidium, and Filobasidium increased significantly in the gut of the diarrheal Baer's Pochard. In conclusion, the current study revealed the discrepancy in gut fungal diversity and community composition between the healthy and diarrheal Baer’s Pochard, laying the basis for elucidating the relationship between diarrhea and the gut mycobiota in Baer’s Pochard.